ANALISIS IMPOR PUPUK DI INDONESIA TAHUN 2004 - 2018 - Anisa Nelva Siti; Mardiana Mardiana; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Indonesia's GDP and the exchange rate affecting the import of Indonesian fertilizer in 2004 - 2018. This study uses secondary data obtained from data from the Central Statistics Agency (BPS) and Bank Indonesia. The analytical method used is Multiple Linear Regression Analysis with the Ordinary Least Square (OLS) least squares analysis, testing of hypotheses and data suitability (classical assumptions) using a 5% significance level. Based on the results of the study it is known that simultaneously Indonesia's GDP and Exchange rates jointly affect Indonesia's fertilizer imports. However, partially, Indonesia's GDP has a positive and significant effect on fertilizer imports in Indonesia and the exchange rate is obtained partially and does not have a significant negative effect on fertilizer imports in IndonesiaKeywords: GDP, Exchange Rate and Fertilizer Import